2018
DOI: 10.1002/app.46540
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive measurement of layer thickness in water‐assisted coinjection‐molded product by ultrasonic technology

Abstract: Layer thickness is an important factor in judging the quality of a water‐assisted coinjection molding (WACIM) part. Here, a novel nondestructive method for measuring layer thickness via ultrasonic technology is proposed. The reflected signals from the interface of a WACIM part were measured by an immersed pulse‐echo method and calculated using a transfer function of the medium. Two objective functions were employed to describe the nonsimilarity between the measured signals and the calculated signals. By solvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Local mechanical properties are also a vital factor in the application of micro parts, such as micro gears . Current testing methods include ultrasonic technology, dielectric sensing, magnetic levitation, and nanoindentation . For example, Zhao et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Local mechanical properties are also a vital factor in the application of micro parts, such as micro gears . Current testing methods include ultrasonic technology, dielectric sensing, magnetic levitation, and nanoindentation . For example, Zhao et al .…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15] Local mechanical properties are also a vital factor in the application of micro parts, such as micro gears. 16 Current testing methods include ultrasonic technology, [17][18][19][20][21] dielectric sensing, 22,23 magnetic levitation, [24][25][26][27][28][29][30] and nanoindentation. 31,32 For example, Zhao et al first found the linear relationship between the degree of crystallinity and the ultrasound velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Layer thickness in a water-assisted co-injection moulding process, which is a process for the production of hollow components with multi-layered walls, has also been investigated by ultrasound sensors [ 37 ]. The authors proposed a model for ultrasound propagation in a layered polymer from a co-injection process.…”
Section: Conventional Ultrasonic Transducer (Ut) Applications In the Injection Moulding Processmentioning
confidence: 99%
“…Injection molding is regarded as the most important method for mass-producing plastic parts [1][2][3][4], and it is complicated because of steep thermal gradients and complex flow geometries; many studies have been conducted in this field [5][6][7][8][9][10]. e product weight of a plastic part is considered one of the most significant properties, especially for plastic parts with high precision requirements, such as plastic lenses.…”
Section: Introductionmentioning
confidence: 99%